SIMULASI TRANSPORTASI TOMAT DAN PERUBAHAN MUTU TOMAT SELAMA PENYIMPANAN - Rozana Rozana; Daud Perdana; Oktavia Nurmawaty Sigiro (Journal of Food Technology and Agroindustry, 2021)
Chemical, physical, and microbiological damage of fruits and vegetables can occur during the transportation process. The percentage of damage can reach 30-50% if the treatment during transportation is not carried out properly. The research objective was to determine the quality changes in tomatoes after transportation simulation based on the arrangement of the fruit in cardboard packaging. The treatment in this research is tomato arrangement patterns: the face centered cubic (FCC) arrangement, the traditional arrangement and the jumble (farmer) arrangement. The research begins with a transportation simulation using a vibrating table in a vertical direction, using a frequency range of 3.9 Hz and an amplitude of 5.2 cm. The simulation is carried out in 1 hour. After the simulation at the 1st hour, amount of mechanical damage (bruising) on ​​every package was carried out. The results showed that the pattern of arranging tomatoes in cardboard packaging that gave the least damage was the FCC arrangement pattern. The FCC pattern only causes shrinkage of 0.11% and the smallest amount of mechanical damage (bruising) is 0.64%.